Dimensional memory in glioblastoma mechanics: traction force analysis of cells cultured in 2D versus 3D collagen environments - Khan, Mishal; Kollenz, Philipp; Fritzenschaft, Maret; Taheri, Fereydoon; Colombo, Federico; Blumberg, Johannes; Schlotterose, Luise; Schwarz, Ulrich S.; Leal-Egaña, Aldo; Selhuber-Unkel, Christine (Bioactive materials, 2025)
Glioblastoma (GB) is one of the most aggressive and lethal brain tumors, characterized by rapid proliferation, diffuse infiltrative growth, therapeutic resistance, and molecular heterogeneity. A major challenge in studying GB is the lack of in vitro models that accurately replicate the tumor's cellular characteristics observed in vivo, particularly the importance of three-dimensional (3D) models. This study investigated the traction stress exerted by LN229 and T98G human GB cell lines, as well as the HMC3 human microglia cell line, using traction force microscopy. First, cells were cultured on two-dimensional (2D) collagen-coated surfaces and within three-dimensional (3D) collagen-based bioactive matrices. Afterward, these cells were extracted and reseeded on flat polyacrylamide gels coated with collagen type I to perform traction force microscopy, thereby directly probing the mechanical memory imparted by their prior 2D or 3D environments. Our findings reveal that GB cells exert substantially higher traction stresses when cultured on 2D collagen-coated surfaces compared to those cultured in 3D bioactive matrices. This underscores the relevance of protein-based bioactive materials, such as collagen scaffolds, in replicating in vivo tumor microenvironments to study GB behavior. Single-cell nanoindentation and focal adhesions quantification were performed to offer mechanistic insights into glioblastoma and microglia cells. Interestingly, in addition to notable differences in traction stresses between cells cultured in 2D and 3D collagen environments, glioblastoma showed significant variation based on the cell type in terms of single-cell stiffness and focal adhesion metrics. These findings underscore the importance of complementary biophysical assays and realistic 3D bioactive matrices when studying GB mechanics in vitro.
Gesehen am 30.01.2026